A hybrid strategy using global analysis of oxidized fatty acids and bioconversion by Bacillus circulans. (9th February 2016) - Sanaki, Takao; Inaba, Yoko; Fujiwara, Takuji; Yoshioka, Takeshi; Matsushima, Keisuke; Minagawa, Kazuyuki; Higashino, Kenichi; Nakano, Toru; Numata, Yoshito
Abstract : Rationale: Targeted oxidized fatty acid analysis has been widely used to understand the roles of fatty acids in the development of diseases. However, because of the extensive structural diversity of fatty acids, it is considered that unknown lipid metabolites will remain undetected. Here, to discover and identify unknown lipid metabolites in biological samples, a global analytical system and a method of synthesizing lipid standards were investigated. Methods: Oxidized fatty acids in mouse lung tissues were extracted using mixed‐mode spin columns. Separation was achieved via ultra‐high‐performance liquid chromatography, mass spectrometric (MS) analysis was conducted in full scan mode using a Q Exactive Plus instrument equipped with an electrospray ionization probe, and structure analysis was carried out by high‐resolution data‐dependent tandem mass spectrometry (dd‐MS 2 ). In addition, lipid standards, which are not commercially available, were synthesized by bioconversion using Bacillus circulans . Results: Oxidized fatty acids in mouse lung tissues were analyzed by high‐resolution accurate‐mass analysis, and multiple unknown molecules were discovered and tentatively identified using high‐resolution dd‐MS 2 . Among these molecules, 21‐hydroxydocosahexaenoic acid (21‐HDoHE) and 22‐HDoHE, which are not commercially available, were synthesized by bioconversion. By comparing the exact masses, retention times, and characteristic fragment ions of the synthesized standards, 21‐HDoHE and 22‐HDoHE were definitively identified in the mouse lung tissue. Conclusions: Our strategy of global analysis and bioconversion can be used for the discovery and identification of unknown lipid molecules. Copyright © 2016 John Wiley & Sons, Ltd.